Improved Mortality of Patients with Gastroschisis: A Historical Literature Review of Advances in Surgery and Critical Care from 1960-2020 - Christina Georgeades; Alyssa Mowrer; Gezzer Ortega; Fizan Abdullah; Jose H. Salazar (MDPI AG, 2022)
The improved survival of gastroschisis patients is a notable pediatric success story. Over the past 60 years, gastroschisis evolved from uniformly fatal to a treatable condition with over 95% survival. We explored the historical effect of four specific clinical innovations-mechanical ventilation, preformed silos, parenteral nutrition, and pulmonary surfactant-that contributed to mortality decline among gastroschisis infants. A literature review was performed to extract mortality rates from six decades of contemporary literature from 1960 to 2020. A total of 2417 publications were screened, and 162 published studies (98,090 patients with gastroschisis) were included. Mortality decreased over time and has largely been <10% since 1993. Mechanical ventilation was introduced in 1965, preformed silo implementation in 1967, parenteral nutrition in 1968, and pulmonary surfactant therapy in 1980. Gastroschisis infants now carry a mortality rate of <5% as a result of these interventions. Other factors, such as timing of delivery, complex gastroschisis, and management in low- and middle-income countries were also explored in relation to gastroschisis mortality. Overall, improved gastroschisis outcomes serve as an illustration of the benefits of clinical advances and multidisciplinary care, leading to a drastic decline in infant mortality among these patients.